Immunomodulatory Effects of Nanoparticles on Skin Allergy - Samreen Jatana (Nature Portfolio, 2017)
Abstract In recent years there has been considerable effort to understand the interaction of nanomaterials with the skin. In this study we use an in vivo mouse model of allergic contact dermatitis to investigate how nanoparticles (NPs) may alter allergic responses in skin. We investigate a variety of NPs that vary in size, charge and composition. Results show that small (<200 nm) negative and neutral charged NPs exhibit an immunosuppressive effect but that positively charged NPs do not. Confocal imaging suggests positively charged NPs may penetrate skin to a lesser extent and thereby are less able interact with and alter the local immune responses. Interestingly, negatively charged silica (20 nm) NPs suppress allergic response to two chemically distinct sensitizers; 1-fluoro-2, 4-dinitrobenzene and 2-deoxyurushiol. Skin wiping and NP application time studies suggest that the immunomodulatory mechanism is not due solely to the blocking of sensitizer adduct formation in skin. Results suggest that NPs modulate early immune events that impact mast cell degranulation. Our study shows for the first time the potential to modulate the elicitation phase of the allergic response which depends on the NP charge and composition. These finding can be used to inform the design topical therapeutics to mitigate allergic responses in skin.